2003
DOI: 10.1017/s003329170300816x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural factors associated with symptom outcomes in a primary care-based depression prevention intervention trial

Abstract: A brief intervention designed to target cognitive-behavioural factors and promote adherence to pharmacotherapy in order to prevent depression relapse was highly successful in changing several behaviours related to controlling depression. Improvements in self-efficacy and several self-management behaviours that were targets of the intervention were significantly related to improvements in depression outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 19 publications
(26 reference statements)
2
87
0
2
Order By: Relevance
“…There is a paucity of strong evidence from appropriately controlled trials that supports the inference from observational studies that SDM regarding treatment of a chronic disease (in which self-management is essential) actually results in patients accepting and adhering to the regimen and improves both treatment adherence and disease outcomes (16,17). Although a recent review of SDM by Joosten and colleagues (18) identified 11 randomized controlled trials that met at least one of Charles and colleagues' criteria, none concerned asthma, and nearly half involved a one-time treatment decision, rather than decisions typical of chronic disease management.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…There is a paucity of strong evidence from appropriately controlled trials that supports the inference from observational studies that SDM regarding treatment of a chronic disease (in which self-management is essential) actually results in patients accepting and adhering to the regimen and improves both treatment adherence and disease outcomes (16,17). Although a recent review of SDM by Joosten and colleagues (18) identified 11 randomized controlled trials that met at least one of Charles and colleagues' criteria, none concerned asthma, and nearly half involved a one-time treatment decision, rather than decisions typical of chronic disease management.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Research studies have examined shared decision-making (SDM) for a variety of illnesses and disabilities, including treatment decisions related to cancer 51 , mental illness 52 , and substance abuse. 53 Results have demonstrated that SDM leads to enhanced patient knowledge and patient satisfaction with treatment choices (Clinical Scenario 4).…”
Section: Shared Decision-making To Optimize Medica-tion Usementioning
confidence: 99%
“…These decision tools can include interactive balance scales that list the pros and cons of a decision, allowing patients to attach their own values to each outcome [49], and personal testimonials to depict how individuals made decisions consistent with their values [50], and can provide quantitative estimates of risks, benefits, and harm that can be tailored to the individual to help patients identify preferences [51,52]. When clinicians collaborate with patients, engage in values clarification, and deliberate with patients, this allows patients to process information and apply knowledge; these processes can lead to greater satisfaction and trust, and even bolster treatment adherence in some contexts [7,[53][54][55][56][57]. Explicit values clarification can help clinicians and patients better understand each other's perspectives on decision and options.…”
Section: The Process Of Shared Decision Making In Oncology Practicementioning
confidence: 99%